Testing and Assessment of Protocols and Systems Modeled as Extended Finite State Machines - Salameh, Tariq Mohammad (2013)
A Master of Science thesis in Computer Engineering by Tariq Mohammad Salameh entitled, "Testing and Assessment of Protocols and Systems Modeled as Extended Finite State Machines," submitted in June 2013. Thesis advisor is Dr. Khaled El Fakih. Available are both soft and hard copies of the thesis.